Social and political foundations of constitutions - Galligan, D. J. (Denis James), 1947-; Versteeg, Mila, 1983- (New York, NY : Cambridge University Press, 2013)
'This volume analyses the social and political forces that influence constitutions and the process of constitution making. It combines theoretical perspectives on the social and political foundations of constitutions with a range of detailed case studies of constitution making in nineteen different countries. In the first part of the volume, leading scholars analyze and develop a range of theoretical perspectives, including constitutions as coordination devices, mission statements, contracts, products of domestic power play, transnational documents, and as reflection of the will of the people. In the second part of the volume, these theories are examined through in-depth case studies of the social and political foundations of constitutions in countries such as Egypt, Nigeria, Japan, Romania, Bulgaria, New Zealand, Israel, Argentina, and others. The result is a multidimensional study of constitutions as social phenomena and their interaction with other social phenomena. The approach combines social science analysis of the nature of constitutions with case studies of selected constitutions'--
Explaining the constitutionalization of social rights : Portuguese hypotheses and a cross national test / Pedro Magalhaes -- Popular constitution making : the case of Iceland / Anne Meuwese -- Romania's transnational constitution : a tradition of elite learning and self-empowerment / Christina Parau -- The social and political foundations of the Nigerian constitution / Charles H. Parkinson -- The once and future democracy : Argentina at the bar of constitutionalism / Miguel Schor -- Battle between law and society in Micronesia / Brian Z. Tamanaha -- Constitutionalism of shallow foundations : the case of Bulgaria / Daniel Smilov -- The shifting foundations of the European Union constitution / Neil Walker.
Includes bibliographical references and index.
Keywords: Constitutional law -- Social aspects; Constitutional law -- Political aspects; Constitutions